Compras públicas sustentáveis na UTFPR: estudo de caso do campus Curitiba – sede reitoria - Galli, Alessandra (2014)
This research focuses on the analysis of public procurements made by the Federal Technology University of Paraná (Universidade Tecnológica Federal do Paraná - UTFPR) from the perspective of the Sustainable Society, the Technological Education and the Science of Law. The main objective was to verify by applying these guiding theoretical aspects – named herein as Analysis Units – whether UTFPR purchases can be considered as Sustainable Public Procurements. The methodology employed for it has been a case study based on a mixed type (quantitative and qualitative) exploratory and descriptive research. Based on the analysis of 507 records of electronic auctions conducted by UTFPR in the chosen period, it was found that, out of the 14,758 items purchased, very few of them contained specific references to sustainability. According to these results, reference guidelines were specifically drawn for the case of the UTFPR Public Procurements. The purpose has been to contribute to this higher education technological institution o that it can demonstrate a clear commitment with the current rules and principles of Environmental Law and the Sustainable Society, becoming a model for other institutions performing public procurement.